How to Study Socially Monogamous Behavior in Secretive Animals? Using Social Network Analyses and Automated Tracking Systems to Study the Social Behavior of Prairie Voles - Sabol, Anne C.; Solomon, Nancy G.; Dantzer, Ben (Frontiers in Ecology and Evolution, 2018)
Accurately recording the social and mating behavior of wild animals is necessary to test hypotheses regarding the evolution of monogamous behavior but documenting the behavior of most wild animals is challenging. Social network analyses can use patterns of spatial and temporal co-occurrence to describe the social associations of individuals within a population, such as which opposite-sex individuals are found together more frequently than others as an indicator of their degree of social monogamy. Social networks generated using automated radio frequency identification (RFID) tracking systems may provide insights into the social behavior of secretive animals because they enable the automated and continuous tracking of the social associations among individuals, which can address many of the limitations with studying these kinds of species. We assessed the potential for social networks generated using an automated RFID tracking system to describe the social behavior of prairie voles (Microtus ochrogaster) in semi-natural enclosures. Our aim was to assess whether social networks generated using the RFID system provided meaningful insights into the social behavior of voles by comparing this method to other methods that have been traditionally used in laboratory (partner preference tests) or field (degree of home range overlap) studies to study social monogamy in prairie voles. In partner preference tests conducted in the field, females spent more time with males with which they had stronger social network associations. Voles that had stronger social network associations also had home ranges that overlapped considerably more than dyads with lower social network associations. In addition, social networks generated from live-trapping and RFID data were comparable but social networks generated using data from our RFID system recorded almost twice as many social associations overall. Our results show that social association metrics derived from social networks generated using the RFID tracking system reflect other commonly used measures of social monogamy in prairie voles. Overall, this suggests that patterns of spatial and temporal co-occurrence are meaningful measures of social monogamy in wild animals.